Encapsulating the delivery of affordable housing: An overview of Malaysian practice - Jamaluddin Nor Baizura; Abdullah Yusfida Ayu; Hamdan Hazlina (MATEC Web of Conferences, 2016)
Urban population increases much faster than other geographical areas and this brings huge challenges to Malaysian government especially those responsible for the provision of housing. Moreover, the rise of living cost and pressure towards the current economic situation had inevitably led to huge demands for affordable housing. Thus, affordability and inaccessibility of people in owning a house has become one of the major issues in Malaysia. These issues are not only faced by the low-income group but mostly experienced by urban dwellers including the middle-income group whom are not eligible to apply for low-cost housing delivered by the government, yet cannot afford to buy a house. Hence, the Malaysian government had therefore established the Perumahan Rakyat 1 Malaysia (PR1MA) as the catalyst in providing adequate, quality and affordable houses. Furthermore, the Syarikat Perumahan Negara Berhad (SPNB) and the state governments also play their big role in providing affordable house at the state level. In trying to ensure smooth delivery of affordable housing, a systematic approach is required. This paper intends to examine the delivery of affordable housing in Malaysia. The objective was to assess the parties involved, and the various stages of the process. The methodology adopted for this study includes in-depth interviews with affordable housing agencies. Investigation showed that the major problem relates to a mismatch in the delivery of affordable housing. Moreover, the political and economic aspects, as well as the organization situation had also influenced the inefficiency of affordable housing delivery system. Additionally, the significant of this paper is expected to formulate an improved strategy and guidance in delivery system, thus ensuring that the method of practice is applicable throughout the country.